2014
DOI: 10.1093/nar/gku533
|View full text |Cite
|
Sign up to set email alerts
|

CBP and p300 acetylate PCNA to link its degradation with nucleotide excision repair synthesis

Abstract: The proliferating cell nuclear antigen (PCNA) protein serves as a molecular platform recruiting and coordinating the activity of factors involved in multiple deoxyribonucleic acid (DNA) transactions. To avoid dangerous genome instability, it is necessary to prevent excessive retention of PCNA on chromatin. Although PCNA functions during DNA replication appear to be regulated by different post-translational modifications, the mechanism regulating PCNA removal and degradation after nucleotide excision repair (NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 69 publications
2
70
0
Order By: Relevance
“…Because p300 in the nucleus has been shown to exist as either a soluble form or a chromatin-bound form [17], we separated the nuclear protein into a soluble fraction and a chromatin-bound fraction. Although the chromatin-bound form of p300 represented a much smaller proportion of the entire nuclear p300 pool, the chromatin-bound p300 is likely to be important in the DNA damage response (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because p300 in the nucleus has been shown to exist as either a soluble form or a chromatin-bound form [17], we separated the nuclear protein into a soluble fraction and a chromatin-bound fraction. Although the chromatin-bound form of p300 represented a much smaller proportion of the entire nuclear p300 pool, the chromatin-bound p300 is likely to be important in the DNA damage response (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our observations in the present study, p300 was shown to be recruited at the sites of DNA break induced by UV or IR in human cells and facilitate DNA repair. Although p300 cannot promote DNA repair by itself, p300 has been considered to serve as a cofactor for multiple mechanisms of DNA repair synthesis [6, 17, 23, 24]. For instance, proliferating cell nuclear antigen (PCNA) is known to accumulate at the radiation-induced DNA damage sites and promote subsequent DNA repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with these conclusions, it has been recently reported that excessive retention of DNA replication and repair factors on chromatin is dangerous for genome stability [46,47]. In particular, mutant forms of PCNA protein that could not be disassembled from chromatin, showed a reduced DNA repair efficiency [48]. Future investigations are needed to elucidate the link of this phenomenon with DS in order to fully clarify the molecular basis of genetic instability in this disease.…”
Section: Discussionmentioning
confidence: 58%
“…We also note a slower migrating PCNA band that copurifies with the ALKBH2 Q10K variant. While the exact nature of the higher molecular weight PCNA band is currently unknown, the additional PCNA species could represent an acetylated form of PCNA based upon its migration [24]. By using a restriction enzyme-mediated AlkB DNA repair assay, the ALKBH2 variants display comparable enzymatic activity to WT ALKBH2 (Figure 3C and D).…”
Section: Resultsmentioning
confidence: 99%